2004
DOI: 10.1103/physrevb.69.060503
|View full text |Cite
|
Sign up to set email alerts
|

Power spectrum of many impurities in ad-wave superconductor

Abstract: Recently the structure of the measured local density of states power spectrum of a small area of the Bi2Sr2CaCu2O8 (BSCCO) surface has been interpreted in terms of peaks at an "octet" of scattering wave vectors determined assuming weak, noninterfering scattering centers. Using analytical arguments and numerical solutions of the Bogoliubov-de Gennes equations, we discuss how the interference between many impurities in a d-wave superconductor alters this scenario. We propose that the peaks observed in the power … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
78
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 20 publications
(46 reference statements)
3
78
0
Order By: Relevance
“…Calculations of QPI from single site and multiple impurities 29,32,[42][43][44] reproduce the locations of experimentally measured wavevectors, but the features in the QPI pattern are "streak-like" rather than "point-like" as in experiment. Zhu et.al 45 studied QPI from multiple impurities, and highlighted the need for more realistic impurity models. Other works have shown that many of the discrepancies between theory and experiment can be resolved by considering an extended long range impurity model, 46 or by including a spatially inhomogeneous chemical potential and superconducting gap.…”
Section: Single Site Impurity Scatteringmentioning
confidence: 99%
“…Calculations of QPI from single site and multiple impurities 29,32,[42][43][44] reproduce the locations of experimentally measured wavevectors, but the features in the QPI pattern are "streak-like" rather than "point-like" as in experiment. Zhu et.al 45 studied QPI from multiple impurities, and highlighted the need for more realistic impurity models. Other works have shown that many of the discrepancies between theory and experiment can be resolved by considering an extended long range impurity model, 46 or by including a spatially inhomogeneous chemical potential and superconducting gap.…”
Section: Single Site Impurity Scatteringmentioning
confidence: 99%
“…This Tripartite structure defines three different regions that are each associated with three different q -space excitations, examples of which are shown in figure 2. In red at low energies is the dispersive QPI, which are excitations from the superconducting ground state likely caused by weak scattering 5,10,32 . Above these states in energy is the non-dispersive q 1 * modulation whose -3 dB intensity corresponds to the end of the kink in the mean LDOS(E) 11 .…”
Section: Calculated Bymentioning
confidence: 99%
“…Very recently Anderson and Hedegård [17] also study the quantum interference between multiple impurities for a d x 2 −y 2 -wave superconductor, whose pairing state could become d x 2 −y 2 + id xy or d x 2 −y 2 + is-wave at some doping level. Our dilute multi-impurity regime discussed above is fundamentally different from that any one else [15][16][17] has studied. Let the length scale between the impurities be d 0 , and the distance away from the impurities, where we are interested, be d. Our interesting regime is then d 0 ∼ d > ∼ 20a (see Fig.…”
mentioning
confidence: 99%
“…The case of multiple impurities for BSCCO is recently considered by Morr et al [15] and Zhu et al [16]. Very recently Anderson and Hedegård [17] also study the quantum interference between multiple impurities for a d x 2 −y 2 -wave superconductor, whose pairing state could become d x 2 −y 2 + id xy or d x 2 −y 2 + is-wave at some doping level.…”
mentioning
confidence: 99%